Dental caries status and treatment need among pregnant women attending antenatal clinics in Dar-Es-Salaam region, Tanzania - Farizana R. Msagati; Godbless J. Mandari; Elison N. M. Simon (BMC, 2024)
Abstract Background Literature shows that pregnant women are more susceptible to dental caries due to several reasons, including changes in salivary flow, reduced pH in the oral cavity, and sugary dietary cravings. The unmet need for care is of special concern, as the failure to obtain treatment can affect the health status of the mother and her unborn child. Objectives To determine dental caries status and treatment needs among pregnant women attending antenatal clinics in the Dar-es-Salaam region. Materials and methods A descriptive cross-sectional hospital-based study was conducted among 461 pregnant women aged 14-47 years. Informed consent was obtained from participants during data collection. Dental caries status and treatment need were diagnosed according to the WHO criteria. The Data collected was cleaned and analyzed using SPSS version 23.0 software for generating frequency distribution tables, chi-square tests, and logistic regression analysis. The Confidence Interval was 95% (p < 0.05). Results The overall prevalence of dental caries was 69%, with a mean DMFT score of 2.86 (± 3.39). Untreated dental decay was observed in 60.5% of study participants, which needed more restorative treatment (fillings & RCT) than a tooth extraction. Caries experiences differed significantly among the pregnant women in various gravidity. In logistic regression, dental caries experience was significantly higher among multigravida respondents (p-values = 0.04) (OR: 1.840, CI 1.021-3.319). Conclusion This study demonstrated a high level of dental caries experience and the presence of treatment needs. Multiple pregnancies were a major factor that contributed to high levels of dental caries.